Determinants for sustainable green product consumption: A glimpse from Peninsular Malaysia - Rian, F. W.; Nawanir, Gusman; Fatimah, Mahmud (AIP Publishing, 2021)
The increase of economic growth changes the lifestyle and consumption patterns. It may also have excessive impact on environmental. One of solution that can be offered is the development of environmental-friendly production and consumption systems. In this study, the perception will be used as initial hypotheses that consumption values are the driving for sustainable green product consumption. Consumption values used are value for money, social value, conditional value, and epistemic value. Environmental attitude which is an independent variable is made as the only first-order construct. The data collection method used in this study is to use a structured questionnaire. To test the hypotheses in this study Structural Equation Modeling (SEM) with SmartPLS 3.3.2 was used. The results shows that the environmental attitude will affect the level of consumption values. More importantly, sustainable green product consumption is not directly affected by social value, and the social value does not mediate the effect of environmental attitudes on sustainable green product consumption. Implication of the research will be discussed.